Promoting Preschool Pre-service Teachers’ Understanding of Food Additives Using the Debate Method - Ganime Aydin; Deniz Saribas (Journal of Education in Science, Environment and Health)
The aim of this research is to investigate the development of preschool education pre-service teachers’ (PST) understanding and evaluation of a socio-scientific topic, namely food additives by using debate as a teaching technique. Qualitative research was designed in a case study model with purposeful sampling in which sixty PST attended Mother and Child Nutrition course. We used qualitative data instruments including pre- and post-reflective forms (RF), assignment papers and video recordings. Data were analyzed using open coding and cross coding. The results indicated that PST’s opinions about food additives may change with the use of debate and scientific articles. The findings also showed that it can be possible to improve their understanding of scientific knowledge about food additives, sources of information, evaluation of sources of information with the help of well-designed debate applications. The evaluation of the components of evidence, sources of evidence, arguments, and expert judgment as well as inclusion of these components in teacher education programs are recommended for further research